Time and timelessness : temporality in the theory of Carl Jung - Yiassemides, Angeliki (Research in analytical psychology and Jungian studies series., 2014)
Time and Timelessness examines the development of Jung's understanding of time throughout his opus, and the ways in which this concept has affected key elements of his work. In this book Yiassemides suggests that temporality plays an important role in many of Jung's central ideas, and is closely interlinked with his overall approach to the psyche and the cosmos at large. Jung proposed a profound truth: that time is relative at large. To appreciate the whole of our experience we must reach beyond causality and temporal linearity, to develop an approach that allows for multidimensional and synch.